The Perceptions of Community on The Role of Kijing Taiwan (Anodonta woodiana) in Freshwater Aquaculture Ponds - Dyah Ayu Wijayanti; Asus Maizar Suryanto Hertika; Bagyo Yanuwiadi (Graduate Program, 2017)
Kijing Taiwan (Anodonta woodiana) is one type of shellfish that live in freshwater, are filter feeders, have high endurance life, and exist in abundant number making Kijing Taiwan can be used as indicators of water pollution that can assist in purifying water. The study is descriptive qualitative, and data is obtained by measuring public perceptions using Likert scale. The later stage begins with determining the respondents. Respondents consist of 27 people from 76 citizen members of the UPR Source Mina fish seed producers and are over 30 years old. The results show that people tend to behave negatively towards Kijing Taiwan by removing and exterminating Kijing Taiwan en masse, as it has been assumed to reduce the cultivation of fish seed. They do not have enough knowledge about the role of Kijing Taiwan leading them to have the wrong perception on the role of Kijing Taiwan in aquaculture ponds. Formulating the strategic management of freshwater aquaculture waters must be done by proposing stakeholders to conduct public education and to convey the results of research on Kijing Taiwan, among other on the role of Kijing Taiwan to help early detection of pollution and as water purifier in aquaculture ponds naturally. Keywords: Benefits of Kijing Taiwan, Public Perception